The Virtuous Circle of Geodiversity: Application of Geoscience Knowledge for Sustainability in the Framework of the International Geodiversity Day - Khoso Rasool Bux; Negri Arianna; Guerini Michele; Mantovani Alizia; Shajahan Rasia; Gentilini Sara; Perotti Luigi; Giardino Marco (Quaestiones Geographicae)
Since geodiversity encompasses a broad spectrum of the Earth’s natural features and provides essential ecosystem services, it plays a critical role in environmental conservation, cultural heritage enhancement, and sustainable development of the territory. This paper presents possible geodiversity actions (use of digital knowledge, geosite inventory, sustainable geotourism, and legislative recognition) through global, regional, and local examples: a series of research and public engagement initiatives, including the themes of the International Geodiversity Day (IGD), a UNESCO celebration aimed at fostering public awareness of the contribution of abiotic nature to daily life and environmental stability. The paper uses a case study approach to present a virtuous circle of geodiversity model that shows how geodiversity can be used to improve environmental stewardship, sustainable resource use, and cultural identity. The interdependences of geological conservation, ecosystem services, and public education in meeting the sustainable development goals (SDGs) of the United Nations are stressed by this model. They underscore the importance of getting public and policy support from which geodiversity benefits can be sustained and suggest strategies for integrating geological diversity into conservation practice. Geodiversity is found to be a critical natural resource and a driver of sustainable development, thus serving communities, economies, and ecosystems.